1993
DOI: 10.1128/jvi.67.12.7140-7148.1993
|View full text |Cite
|
Sign up to set email alerts
|

Escape from in vivo restriction of Moloney mink cell focus-inducing viruses driven by the Mo+PyF101 long terminal repeat (LTR) by LTR alterations

Abstract: is a variant Moloney murine leukemia virus containing polyomavirus F101 enhancers inserted just downstream from the M-MuLV enhancers in the long terminal repeat (LTR). The protein coding sequences for this virus are identical to those of M-MuLV. Mo+PyF101 M-MuLV induces T-cell disease with a much lower incidence and longer latency than wild-type M-MuLV. We have previously shown that Mo+PyF101 M-MuLV is defective in preleukemic events induced by wild-type M-MuLV, including splenic hematopoietic hyperplasia, bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…LTR enhancer sequences are crucial determinants of this property (15,27,35,41,50,52,64,98). They appear to act at multiple steps in the process of lymphomagenesis, including viral replication in hematopoietic tissues, preleukemic hyperplasia, and proto-oncogene activation (5,8,9,19,21,25,38,64,78,97). The sequence that contains the Ets site (ACAGG ATATC) is identical in SL3 and Mo-MuLV (28).…”
Section: Discussionmentioning
confidence: 99%
“…LTR enhancer sequences are crucial determinants of this property (15,27,35,41,50,52,64,98). They appear to act at multiple steps in the process of lymphomagenesis, including viral replication in hematopoietic tissues, preleukemic hyperplasia, and proto-oncogene activation (5,8,9,19,21,25,38,64,78,97). The sequence that contains the Ets site (ACAGG ATATC) is identical in SL3 and Mo-MuLV (28).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, deletion of polyomavirus enhancer sequences and the adjacent XbaI site could have converted the MCF virus-diagnostic fragment to viral-cellular junction fragments of indeterminate size. In subsequent studies, we observed both classes of LTR alterations (2,4). The BamHI-ClaI restriction digestion used in these experiments is not influenced by alterations in the MoϩPyF101 M-MuLV LTR.…”
Section: Discussionmentioning
confidence: 71%
“…DNA was extracted from single-cell suspensions or cell lines by a modification of standard methods (8) and suspended in 10 mM Tris-0.1 mM EDTA (pH 8). Restriction endonuclease digestion of high-molecular-weight DNA, gel electrophoresis, transfer, and hybridization were performed as previously described (2,4,6). DNA fragments used as radioactive probes for Southern blot analyses included the 199-bp PyF101 enhancer-containing PvuII-4 fragment inserted at the XbaI site of MoϩPyF101 M-MuLV as previously described (23); the 620-bp BamHI-EcoRI fragment from the 5Ј env region of the M-MCF recombinant that is reactive with the M-MCF recombinant and endogenous polytropic and modified polytropic viruses (6), and the 1.1-kb BamHI-ClaI fragment from the 3Ј env region of M-MuLV that is reactive with both ecotropic M-MuLV and polytropic M-MCF recombinants (4).…”
Section: Methodsmentioning
confidence: 99%
“…The amplification of the LVb-core region has been documented in proviruses of T-lymphoid tumors induced by several other MuLVs or FeLVs (3,5,14,33,35,44,49). In a prior study by Chen and Yoshimura, proviral insertions adjacent to c-myc that had duplications in the MCF 13 enhancers invariably included the core and LVb binding sites (12).…”
Section: Discussionmentioning
confidence: 94%
“…3). However, we and others have detected enhancer alterations in end-stage tumors induced by various MuLV and feline leukemia virus (FeLV) recombinants (3,5,14,33,35,44,49). Thus, a more detailed PCR analysis with SRS-specific oligonucleotide primers was used to search for modifications in the SRS sequences ( Fig.…”
Section: Generation Of ⌬Mo؉srs M-mulvmentioning
confidence: 99%